THE CORRELATION BETWEEN FAMILY ROLES AND LEADING DRIVER IN ARMENIAN WOMEN - Khanamiryan, I. R.; Arakelyan , M. (Modern Psychology, 2019)
The basics of life attitudes, beliefs, relationships and role scenarios lie in childhood. The most important for child’s further life are the attitudes and drivers given by parents, especially by mother. These messages are carefully studied by the representatives of the transactional approach. In particular, T. Kahler identifies 5 main drivers that have a huge impact on the formation of behavioral reactions in adulthood. The article presents a study of the correlation between the drivers and family roles of Armenian women and highlights the dominant drivers leading to certain behavioral patterns.